KONTRUKSI REGULASI ONLINE DISPUTE RESOLUTION DALAM PENYELESAIAN SENGKETA E-COMMERCE - Cahaya Permata; Fauziah Lubis; Mhd. Yadi Harahap (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The significant growth of e-commerce in Indonesia has led to an increased potential for disputes between consumers and business actors, including issues related to product quality, delivery delays, and the protection of personal data. Dispute resolution through judicial mechanisms is considered less responsive to the characteristics of electronic transactions, as it tends to be time-consuming, costly, and inflexible. Therefore, Online Dispute Resolution (ODR) is regarded as a relevant alternative, as it offers a dispute resolution process that is fast, simple, and efficient. This study aims to examine the juridical position of ODR within the Indonesian legal system, assess its effectiveness in resolving e-commerce disputes, and formulate the direction for regulating ODR under national law. The research employs a normative juridical method using statutory and conceptual approaches, based on secondary data consisting of primary and secondary legal materials, which are qualitatively analyzed using inductive reasoning. The findings indicate that ODR has significant potential as a mechanism for resolving e-commerce disputes; however, the absence of explicit normative regulation has created a legal vacuum, particularly with respect to procedural standards, the accountability of ODR providers, and consumer protection. Therefore, clear and comprehensive regulatory strengthening is required concerning electronic evidence-based proof, the authority of ODR providers as neutral fact-finders, and the nature of ODR decisions as final and binding with limited enforceability, accompanied by procedural standardization and personal data protection to ensure legal certainty, justice, and the legitimacy of ODR. Keywords: E-commerce, Regulatory Construction, Online Dispute Resolution, Dispute Resolution. Abstrak: Perkembangan e-commerce yang signifikan di Indonesia berimplikasi pada meningkatnya potensi sengketa antara konsumen dan pelaku usaha, seperti kualitas produk, keterlambatan pengiriman, serta perlindungan data pribadi. Penyelesaian sengketa melalui mekanisme peradilan dinilai kurang responsif terhadap karakter transaksi elektronik karena cenderung memerlukan waktu lama, berbiaya tinggi, dan minim fleksibilitas. Oleh karena itu, Online Dispute Resolution (ODR) dipandang sebagai alternatif yang relevan karena menawarkan proses penyelesaian yang cepat, sederhana, dan efisien. Penelitian ini bertujuan mengkaji kedudukan yuridis ODR dalam sistem hukum Indonesia, menilai efektivitasnya dalam penyelesaian sengketa e-commerce, serta merumuskan arah pengaturan ODR dalam hukum nasional. Penelitian menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan dan konseptual, berbasis data sekunder berupa bahan hukum primer dan sekunder yang dianalisis secara kualitatif dengan penalaran induktif. Hasil penelitian menunjukkan bahwa ODR memiliki potensi besar sebagai mekanisme penyelesaian sengketa e-commerce, namun ketiadaan pengaturan normatif yang tegas menimbulkan kekosongan hukum, khususnya terkait prosedur, akuntabilitas penyelenggara, dan perlindungan konsumen. Maka, diperlukan penguatan regulasi yang jelas dan komprehensif tentang pembuktian berbasis bukti elektronik, kewenangan penyelenggara sebagai pemeriksa fakta yang netral, serta karakter putusan ODR yang bersifat final, mengikat, dan memiliki daya eksekutorial terbatas, disertai dengan standarisasi prosedur dan perlindungan data pribadi untuk menjamin kepastian hukum, keadilan, dan legitimasi ODR. Kata Kunci: E-Commerce, Konstruksi Regulasi, Online Dispute Resolution, Penyelesaian Sengketa.